Data-Driven Insights on the Effects of COVID-19 on Aesthetics: Part I (Passive Analysis). (22nd August 2020) - Chandawarkar, Akash; Jenny, Hillary; Kim, Roy
Abstract: Background: Since COVID-19 was declared to be a worldwide pandemic and US national emergency in March (week 11), it has significantly changed aesthetic plastic surgery. As plastic surgeons now move towards reopening practices, understanding public interest in medical aesthetics will be critical to maximize efforts and resource allocation in procedures and treatments that patients want. Objectives: In this study, the authors sought to passively query public interest in aesthetics utilizing Google Trends search data. Methods: Google Trends was utilized to quantify relative search volumes over the past 4 years for a variety of categories: patient-related, surgery-related, injectables, breast procedures, face procedures, and body procedures. Data were deseasonalized and represented graphically. Z-scores of each time-point differing from the expected values were determined utilizing least squares regression. Results: Of the 204 significantly anomalous search term data points in 2020, 172 (84.0%) occurred after week 11 (pandemic/national emergency declaration). Sixty percent of searches in all time-points after week 11 significantly differed, and 25/26 (96.0%) search terms experienced significant changes after week 11. There was decreased interest for 18 terms with variable recovery. Procedural nadirs for decreased search volume troughs occurred between weeks 11 and 14. Six patient-related chief complaints saw increased search interest after COVID-19, with peak interest between weeks 11 and 17. Conclusions: This is the first study, to the authors' knowledge, to assess real-time, national data about the impact of COVID-19 on public interest in aesthetics.